(untitled) (Confluenţe Bibliologice, 2025)
The article outlines the portrait of the remarkable sociologist and man of culture Dimitrie Gusti, emphasizing his essential contributions to the development of libraries in Romania. Gusti was a fervent supporter of the formative role of reading and specialized libraries, promoting modern ideas regarding the organization of university libraries and free access of readers to knowledge. He initiated and supported numerous projects of rural libraries and encyclopedic collections dedicated to peasants, such as "Cartea Satului". Through his vision, reading becomes an instrument of social and intellectual emancipation.